Discovery of Withaphysalin A and Limonin as Potential SARS-COV2 Papain-Like Protease Inhibitors - Barasa, S. S.; Okenyo , W. O.; Akenga, T. A. O. (Africa Environmental Review Journal, 2022)
Protease inhibitors are strategically and functionally important components of drug-hunters’ arsenal against pathogenic viruses including SARS-COV2, SARS-COV, MERS, Ebola and HIV. Drug discovery efforts reported in this work target the papain-like protease (PLpro) alias non-structural protein 3 (nsp3) of SARS-COV2. An in-house database comprising of 6264 phytochemicals derived from 1560 Kenyan medicinal plants, as well as the COCONUT-Mitishamba database provided phytochemical scaffolds used in this in silico structure-based virtual screening study. Overall, 170 phytochemicals from our in-house database and 58 phytochemicals from the COCONUT-Mitishamba database had desirable binding affinities of less than -9.0 kcal/mol. Withaphysalin A (11.5 kcal/mol) and Limonin (-11.1 kcal/mol) are the best compounds targeting the nsp3 of SARS-COV2 from our in-house database. We studied protein-ligand interactions of top-binding molecules to gain insight on their potential modulatory effects on the SARS-COV2 virus. Although experimental validation of the results obtained and other further tests need to be done, these findings will accelerate the drug design and development process.